The Anti-Inflammatory Effect of Nigella sativa Toothpaste on Porphyromonas gingivalis Bacteria Through Decreased TNF-α, MMP-9, PGE-2 Expression in Wistar Rats - Maduratna, Ernie; Sari, Desi Sandra; Rahayu, Retno Puji; Masya, Resgita Nadila; Adinar, Noor (European Journal of Dentistry, 2024)
Objective The main principle in preventing periodontal disease is to improve oral hygiene. The bacteria that cause the onset of periodontal disease, one of which is the Porphyromonas gingivalis bacterium, causes inflammation. Persistent inflammation causes tissue damage and alveolar bone resorption by secreting proinflammatory cytokines, matrix metalloproteinase-9 (MMP-9), prostaglandin E2 (PGE-2), and anti-inflammatory cytokines. In this case, preventive treatment is needed, such as using toothpaste that contains anti-inflammatories so that the progression of the disease does not get worse. The traditional ingredient currently being developed is Nigella sativa, which has anti-inflammatory properties. Therefore, this study analyzes the potential of toothpaste containing Nigella sativa on the expression of tumor necrosis factor-α (TNF-α), MMP-9, and PGE-2 in the Wistar rat model induced by Porphyromonas gingivalis bacteria. This study aims to prove the potential of Nigella sativa toothpaste to decrease the expression of PGE-2, TNF-α, and MMP-9 in the gingiva of rats induced by Porphyromonas gingivalis bacteria.Materials and Methods Forty-five healthy male Wistar rats were used, consisting of the negative control group, which was only injected with Porphyromonas gingivalis bacteria ATCC3322. The positive control group was given enzyme toothpaste, and the treatment group was assigned 1 mg of Nigella sativa paste using a microbrush for 30 seconds on the gingiva incisors mandibular with a circular motion, given two times a day for a week. Immunohistochemical to see the expression of TNF-α, PGE-2, and MMP-9. Parametric comparative analysis using a one-way analysis of variance test was performed to analyze differences between groups.Results and Discussion Nigella sativa toothpaste significantly reduced proinflammatory cytokines, as seen through the expression of TNF-α, PGE-2, and MMP-9 on days 3, 5, and 7 (p <0.05).Conclusion In the limit of studied animal model, this trial indicates that giving toothpaste with black seed extract (Nigella sativa) could inhibit inflammatory mediators, as seen from the decreased expression of MMP-9, TNF-α, and PGE-2 seen from the 3rd, 5th, and 7th days.
Keywords: anti-inflammatory; periodontitis; Nigella sativa